Hypoxia‐driven Hif2a coordinates mouse liver regeneration by coupling parenchymal growth to vascular expansion. Issue 6 (7th October 2016) - Kron, Philipp; Linecker, Michael; Limani, Perparim; Schlegel, Andrea; Kambakamba, Patryk; Lehn, Jean‐Marie; Nicolau, Claude; Graf, Rolf; Humar, Bostjan; Clavien, Pierre‐Alain
Abstract : Interaction between sinusoidal endothelial cells and hepatocytes is a prerequisite for liver function. Upon tissue loss, both liver cell populations need to be regenerated. Repopulation occurs in a coordinated pattern, first through the regeneration of parenchyme (hepatocytes), which then produces vascular endothelial growth factor (VEGF) to enable the subsequent angiogenic phase. The signals that instruct hepatocytes to induce timely VEGF remain unidentified. Given that liver is highly vascularized, we reasoned that fluctuations in oxygenation after tissue loss may contribute to the coordination between hepatocyte and sinusoidal endothelial cell proliferation. To prevent drops in oxygen after hepatectomy, mice were pretreated with inositol trispyrophosphate (ITPP), an allosteric effector of hemoglobin causing increased O2 release from heme under hypoxic conditions. ITPP treatment delayed liver weight gain after hepatectomy. Comparison with controls revealed the presence of a hypoxic period around the peak of hepatocyte mitosis. Inhibition of hypoxia led to deficient hepatocyte mitosis, suppressed the regenerative Vegf wave, and abrogated the subsequent reconstruction of the sinusoidal network. These ITPP effects were ongoing with the reduction in hepatocellular hypoxia inducible factor 2a (Hif2a). In contrast, Hif1a was unaffected by ITPP. Hif2a knockdown phenocopied all effects of ITPP, including the mitotic deficiencies, Vegf suppression, and angiogenic failure. Conclusions: Oxygen is a key regulator of liver regeneration. Hypoxia—inherent to the expansion of parenchyme—activates Hif2a to couple hepatocyte mitosis with the angiogenic phase. Hif2a acts as a safeguard to initiate sinusoidal reconstruction only upon successful hepatocyte mitosis, thereby enforcing a timely order onto cell type‐specific regeneration patterns. These findings portray the hypoxia‐driven Hif2a‐Vegf axis as a prime node in coordinating sinusoidal endothelial cell‐hepatocyte crosstalk during liver regeneration. (Hepatology 2016;64:2198‐2209).